Mutations in KRT10 in epidermolytic acanthoma. - Cheraghlou, Shayan; Atzmony, Lihi; Roy, Simon F; McNiff, Jennifer M; Choate, Keith A (J Cutan Pathol, 2020)
BACKGROUND: Epidermolytic acanthoma (EA) is a rare acquired lesion demonstrating a characteristic histopathological pattern of epidermal degeneration referred to as epidermolytic hyperkeratosis (EHK). On histopathological analysis, EA appears nearly identical to inherited EHK-associated dermatoses such as epidermolytic ichthyosis and ichthyosis bullosa of Siemens. While it has been speculated that EA is caused by mutations in KRT10, KRT1, or KRT2 found in these inherited dermatoses, none have yet been identified. Herein, we aim to identify the contributions of keratin mutations to EA. METHODS: Using genomic DNA extracted from paraffin-embedded samples from departmental archives, we evaluated a discovery cohort using whole-exome sequencing (WES) and assessed remaining samples using Sanger sequencing screening and restriction fragment length polymorphism (RFLP) analysis. RESULTS: DNA from 16/20 cases in our sample was of sufficient quality for polymerase chain reaction amplification. WES of genomic DNA from lesional tissue revealed KRT10 c.466C > T, p.Arg156Cys mutations in 2/3 samples submitted for examination. RFLP analysis of these samples as well as eight additional samples confirmed the mutations identified via WES and identified four additional cases with Arg156 mutations. In sum, 6/11 screened cases showed hotspot mutation in KRT10. CONCLUSIONS: Hotspot mutations in the Arg156 position of KRT10, known to cause epidermolytic ichthyosis, also underlie EA.
Keywords: Acanthoma; Adult; Aged; Aged, 80 and over; Female; Genomics; Humans; Hyperkeratosis, Epidermolytic; Ichthyosis Bullosa of Siemens; Keratin-10; Keratins; Male; Middle Aged; Mutation; Skin Neoplasms; Whole Exome Sequencing

Post-zygotic ACTB mutations underlie congenital smooth muscle hamartomas. - Atzmony, Lihi; Ugwu, Nelson; Zaki, Theodore D; Antaya, Richard J; Choate, Keith A (J Cutan Pathol, 2020)
BACKGROUND: Congenital smooth muscle hamartomas (CSMHs) are benign lesions that share clinical and histopathological features with Becker nevus, a mosaic disorder associated with post-zygotic ACTB mutations. Given the clinical and histopathological overlap between CSMH and Becker nevus, we hypothesized that post-zygotic mutations in ACTB may underlie CSMH. METHODS: Direct sequencing of ACTB gene in affected and unaffected tissue isolated from one case of hemihypertrichosis and hemihypertrophy corresponding to giant segmental CSMH and hemihypertrophy. This was followed by direct sequencing with and without enrichment assay for hotspot ACTB mutations in affected tissue from 12 samples of isolated CSMH from unrelated individuals. RESULTS: In total we identified somatic missense ACTB mutations in 9 out of 13 CSMHs (69%). Mutations were either novel or previously reported in Becker nevi and Becker nevus syndrome. CONCLUSIONS: CSMHs result from post-zygotic ACTB mutations. This study proves that CSMHs and Becker nevi are nosologically related, and expand the phenotypic spectrum of ACTB mutations.

Topical cholesterol/lovastatin for the treatment of porokeratosis: A pathogenesis-directed therapy. - Atzmony, Lihi; Lim, Young H; Hamilton, Claire; Leventhal, Jonathan S; Wagner, Annette; Paller, Amy S; Choate, Keith A (J Am Acad Dermatol, 2020)
BACKGROUND: Porokeratosis is associated with mevalonate pathway gene mutations. Therapeutic options are few and often limited in efficacy. We hypothesized that topical therapy that aims to replenish cholesterol, an essential mevalonate pathway end-product, and block the accumulation of mevalonate pathway toxic metabolites could alleviate porokeratosis. OBJECTIVE: To study the efficacy of topical cholesterol/lovastatin in different variants of porokeratosis. METHODS: We enrolled a series of 5 porokeratosis patients,1 with disseminated superficial actinic porokeratosis, 2 with porokeratosis palmaris et plantaris disseminata, and 2 with linear porokeratosis. Patients were genotyped before initiation of therapy. Patients then applied topical cholesterol/lovastatin twice daily to a unilaterally defined treatment area for up to 3 months. The response was evaluated and patients photographed at every visit. RESULTS: Three patients had MVD mutations, and 2 patients had PMVK mutations. Treatment with topical cholesterol/lovastatin (but not cholesterol alone) resulted in near complete clearance of disseminated superficial actinic porokeratosis lesions after 4 weeks of therapy and moderate improvement of porokeratosis palmaris et plantaris disseminata lesions and linear porokeratosis lesions. There were no adverse events. LIMITATIONS: Case series design with a small number of patients. CONCLUSION: Topical cholesterol/lovastatin is an effective and well-tolerated therapy for porokeratosis that underscores the utility of a pathogenesis-based therapy that replaces deficient end products and prevents accumulation of potentially toxic precursors.

Two percent lovastatin ointment as a pathogenesis-directed monotherapy for porokeratosis. - Ugwu, Nelson; Choate, Keith A; Atzmony, Lihi (JAAD Case Rep, 2020)

Phenotypic expansion of POFUT1 loss of function mutations in a disorder featuring segmental dyspigmentation with eczematous and folliculo-centric lesions. - Atzmony, Lihi; Zaki, Theodore D; Antaya, Richard J; Choate, Keith A (Am J Med Genet A, 2019)
Appearance of mosaic disorders in thin Blaschko lines suggests that somatic mutations in keratinocyte precursors underlie their pathogenesis. Germline heterozygous mutations in POFUT1 gene cause Dowling-Degos disease (DDD), a skin disease that features flexural reticulated hyperpigmentation and follicular-based lesions. POFUT1 mosaicism has not been described to date. Here, we describe a 9-year-old female with segmental hyper- and hypopigmented patches with overlying eczematous plaques and follicular papules. Employing paired whole exome sequencing of saliva and keratinocytes isolated from affected skin, we found a novel germline heterozygous POFUT1 deletion causing frameshift and premature codon termination and somatic copy-neutral loss of heterozygosity on chromosome 20 encompassing POFUT1. Expression levels of POFUT1 as well as other key regulators of the notch signaling pathway-NOTCH1, NOTCH2, and HES1-were reduced in affected keratinocytes compared with normal keratinocytes. Our findings provide the first evidence of POFUT1 postzygotic mutation and a phenotypic expansion of POFUT1 loss of function mutations. We show that a recessive loss of function mutation in POFUT1 produces a distinct clinical presentation with features (e.g., dermatitis) that are absent in the generalized form of DDD. This study demonstrates how analysis of mosaic disorders can reveal unexpected phenotypes for known genes.